Analisis Potensi Bahaya dan Pengendalian K3 di Sandtrap dan Heifer PT. Q Menggunakan Metode FMEA - Dinda Maharani Saszia Putri; Teguh Taruna Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Occupational Safety and Health is a crucial aspect in operational activities in the industrial sector, including the livestock industry such as PT. Q. In large-scale livestock activities, potential hazards to workers, livestock, and the surrounding environment can arise from various routine activities, such as waste processing and maintenance of existing facilities. Therefore, the implementation of an OHS system is needed to minimize work risks and ensure the continuity of safe and efficient operations. This study aims to determine the risk of work accidents, classify potential hazards, and evaluate and provide additional risk controls in the sandtrap and heifer areas of PT. Q. The FMEA method has the advantage of being able to explain various risks in detail and comprehensively, helping to improve future work, and is able to identify accident risks based not only on one criterion, but also on three criteria: severity, frequency of occurrence, and detectability. The data collection used was obtained from interviews with 7 respondents, observations, and documentation. The data collection techniques used were interviews and direct practice. Therefore, some suggestions that can be given are using remote operator tools in the machine operator section, adding protection to the screen section and moving roller separator machines, carrying out routine maintenance on the roads used, installing K3 signs in every road traffic, providing first aid kits in every department, and providing K3 socialization to all company staff involved.